Anne Frank [videorecording (DVD)] - Dornhelm, Robert; Kingsley, Ben, 1943-; Blethyn, Brenda, 1946-; Taylor-Gordon, Hannah; Blacher, Tatjana; Król, Joachim, 1957-; Taylor, Lili; Müller, Melissa, 1967- (Buena Vista Home Entertainment, 2001)
Dramatization of the life and death of Anne Frank.